METHOD FOR DETERMINING MAXIMUM LAKE LEVELS IN THE ABSENCE OF OBSERVATIONAL DATA (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
In the article the methodology for calculating the maximum water levels of unexplored lakes is considered, based on the generalization of all available information on the regime of the lakes of the studied area. Recommendations are given for calculating the parameters of the distribution of the maximum levels of unexplored lakes in the North-West of the Russian Federation and the southern part of the Kola Peninsula.
Keywords: lakes; specific watershed; maximum water levels; distribution parameters